2021
DOI: 10.3390/ijerph18115708
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of School Start Times, Sleep Duration and Mental Health among a Representative Sample of High School Students in Colorado, 2019

Abstract: This cross-sectional study utilized responses from 46,537 students enrolled in grades 9 through 12 in 166 high schools across the state of Colorado via the 2019 Healthy Kids Colorado Survey to: (1) quantify the association between high school start times and student sleep duration and (2) investigate the associations between school start times and student mental health. Descriptive and bivariate analyses were used to investigate associations between school start times and self-reported demographic, sleep, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…Yet, unlike that study, insufficient sleep was not significantly associated with seriously considering suicide in our sample after adjusting for risk and protective factors. This finding aligns with past studies demonstrating that depressive symptoms explained the relationship between insufficient sleep and suicidal ideation ( 4 , 23 ). Given these inconsistent findings, additional research capturing a broader range of outcomes, including anxiety and resilience, is needed to fully investigate the implications of insufficient sleep on mental health.…”
Section: Discussionsupporting
confidence: 93%
“…Yet, unlike that study, insufficient sleep was not significantly associated with seriously considering suicide in our sample after adjusting for risk and protective factors. This finding aligns with past studies demonstrating that depressive symptoms explained the relationship between insufficient sleep and suicidal ideation ( 4 , 23 ). Given these inconsistent findings, additional research capturing a broader range of outcomes, including anxiety and resilience, is needed to fully investigate the implications of insufficient sleep on mental health.…”
Section: Discussionsupporting
confidence: 93%
“…In fact, delaying school start times has been shown to increase adolescents’ sleep duration and improve academic performance [ 85 , 86 ]. Studies found that a 15-minute delay in school start times was associated with a 5-minute increase in sleep duration [ 87 ] and a 50-minute delay was associated with a 43-minute increase [ 88 ].…”
Section: Discussionmentioning
confidence: 99%
“…2,3 In an effort to improve mental health outcomes, boards may guide school day start times to accommodate students' natural sleep patterns. 4 In addition, boards shape the built environment through investments in air filters, air conditioning systems, and protection from excessive sun exposure. Significantly, their influence extends to health care: from hiring schoolbased health professionals and fostering partnerships with county health offices to supporting comprehensive school-based health services that span preventative, acute, and emergency care.…”
Section: School Boards Shape Student Healthmentioning
confidence: 99%
“…For example, boards interpret and implement federal guidelines for cafeteria nutrition, a lever for addressing rates of obesity . In an effort to improve mental health outcomes, boards may guide school day start times to accommodate students’ natural sleep patterns . In addition, boards shape the built environment through investments in air filters, air conditioning systems, and protection from excessive sun exposure.…”
Section: School Boards Shape Student Healthmentioning
confidence: 99%